Self-deception and self-knowledge: Jane Austen’s Emma as an Example of Kant’s Notion of Self-Deception - Grenberg, Jeanine M. (Con-Textos Kantianos. International Journal of Philosophy, 2015)
In this paper, I address the theme of harmony by investigating that harmony of person necessary for obtaining wisdom. Central to achievement of that harmony is the removal of the unstable, unharmonious presence of self-deception within one’s moral character.